Implementation of Sharia Investment in Islamic Banking: Analysis of Principles, Contracts, and Challenges in Strengthening the Islamic Financial System - Fatih Siraj; Pani Akhiruddin Siregar; Ahmad Afandi Surbakti (Al Urwah : Sharia Economics Journal, 2025)
The development of Islamic banking in Indonesia has shown significant growth, with Islamic investment serving as a key pillar in strengthening the Sharia-based financial system. However, its implementation still faces challenges, including low Islamic financial literacy, limited product innovation, and the need to strengthen governance and risk management. This study aims to analyze the implementation of Islamic investment in Islamic banking by examining its principles, contracts, and challenges in supporting Sharia economic growth. The research employs a qualitative approach using a literature study method by reviewing and analyzing relevant scientific sources related to Islamic investment and banking practices. The results indicate that Islamic investment based on mudharabah, musyarakah, murabahah, and ijarah contracts plays an important role in improving Islamic banking performance, particularly when supported by technological innovation and adequate regulatory frameworks. In conclusion, strengthening financial literacy, enhancing product innovation, and improving governance are essential strategies to optimize Islamic investment and promote the sustainability of Islamic banking in supporting national economic development.